Efecto de los campos eléctricos sobre la producción de biomasa micelial del hongo medicinal Ganoderma lucidum [(W. Curt.: Fr.) P. Karst. (Ganodermataceae)] (2010)
ABSTRACT: The effect of electric fields on the growth of the fungus Ganoderma lucidum [(W. Curt.: Fr) P. Karst. Ganodermataceae] under submerged culture was evaluated in order to optimize the production of biomass. Ganoderma lucidum was exposed to three different factors, types of electric elds [alternating current (AC), direct current (DC) and pulsed current (IM)], eld intensities from 0.0 kV cm-1 (control culture) to 3.0 kV cm-1, stimulation period depending on the growth phase of the fungus after inoculation: day 0 (lag phase), day 3 (exponential or log phase) and day 6 (stationary phase). Results showed that the combination of three factors: AC electric eld at an intensity of 1.5 kV cm-1 applied at day 3 day the highest biomass production with an average of 35.6450 ± 0.6684 g l-1, whereas the combination of DC electric eld at an intensity of 2.5 kV cm-1 applied at day 6 showed the lowest production of biomass with an average of 26.2950 ± 3.9926 g l-1. These results show that depending on the combination of evaluated factors, the production of biomass of the fungus Ganoderma lucidum in submerged culture conditions may be stimulated by applying electric elds.